2000
DOI: 10.1111/j.1752-1688.2000.tb04299.x
|View full text |Cite
|
Sign up to set email alerts
|

PLANNING FOR DROUGHT: MOVING FROM CRISIS TO RISK MANAGEMENT1

Abstract: Severe drought is a recurring problem for the United States, as illustrated by widespread economic, social, and environmental impacts. Recent drought episodes and the widespread drought conditions in 1996, 1998, and 1999 emphasized this vulnerability and the need for a more proactive, risk management approach to drought management that would place greater emphasis on preparedness planning and mitigation actions. Drought planning has become a principal tool of states and other levels of government to improve th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
153
0
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 253 publications
(160 citation statements)
references
References 6 publications
1
153
0
6
Order By: Relevance
“…Numerical prediction is valuable to proactively manage risks in areas such as hydropower, drinking water production and drought preparedness (Wilhite et al, 2000). Regardless of the application, probabilistic forecasts are preferred over deterministic ones to convey uncertainties (Krzysztofowicz, 2001;Ramos et al, 2013).…”
Section: Approaches To Seasonal Streamflow Forecastingmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerical prediction is valuable to proactively manage risks in areas such as hydropower, drinking water production and drought preparedness (Wilhite et al, 2000). Regardless of the application, probabilistic forecasts are preferred over deterministic ones to convey uncertainties (Krzysztofowicz, 2001;Ramos et al, 2013).…”
Section: Approaches To Seasonal Streamflow Forecastingmentioning
confidence: 99%
“…Research has shown that the relative role of each source of predictability mainly depends on the "inertia" or "memory" of the studied basin, the forecast season and the forecast lead time (Wood and Lettenmaier, 2008;Shukla et al, 2013;Yossef et al, 2013;Wood et al, 2016). Yossef et al (2013) showed that in western Europe, from July to October, streamflow forecasts are more dependent on meteorolog-ical forcing than they are on initial conditions, even 1 month ahead.…”
Section: Approaches To Seasonal Streamflow Forecastingmentioning
confidence: 99%
“…On the contrary, we should take a proactive approach to dealing with drought, anticipating the occurrence of the natural phenomenon and planning measures for minimizing its negative effects (Wilhite et al, 2000). However, making the transition from crisis to risk management is difficult because little has been done to understand and address the risks associated with drought, and to identify the factors that influence the vulnerability of a region to dry spells (Wilhite, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…US drought risk management focuses on the need for improved proactive strategies that can be implemented before an event occurs to reduce impacts during future droughts and increase the timeliness and effectiveness of response (Wilhite et al 2000a). In this context, drought monitoring and early warning is one component of a drought risk management approach.…”
Section: The Issue Of Triggers: the Us Scientist's Perspectivementioning
confidence: 99%